The Effect of Dosage and Frequency of Potassium Fertilization on the Growth and Yield of White Eggplant (Solanum melongena L. var. Kania) - Kholid Ihsan Abdulloh; Ramdan Hidayat; Pangesti Nugrahani (The University of Lampung, 2025)
Eggplant plants have a high flower drop rate, resulting in a low fruit set. Potassium fertilizer plays an important role in plant physiology and can help reduce flower drop. This study aims to determine the effect of dosage and frequency of potassium fertilization on the growth and yield of white eggplants. The research was conducted in Mojosari District, Mojokerto Regency, East Java, from December 2023 to March 2024. This research was a factorial study with two factors arranged in a Completely Randomized Design. The first factor is potassium fertilizer dosage, which included 3 levels (3, 6, and 9 g/plant), and the second factor is fertilization frequency, which included 3 levels (2, 3, and 4 times). Results showed that the combination of potassium fertilizer dosage of 9 g/plant with potassium fertilization frequency of 4 times was the best treatment combination for fruit weight per plant, with an increase of 114% compared to the combination of potassium fertilizer dosage of 3 g/plant and potassium fertilization frequency of 2 times.